Description of fourth instar larva and pupa of Atrichopogon delpontei Cavalieri and Chiossone (Diptera: Ceratopogonidae) from Brazilian Amazonia - Marino, Pablo Ignacio (2017)
The fourth instar larva and pupa of Atrichopogon delpontei Cavalieri and Chiossone are described for the first time. The immatures were collected from stream margins in the northern Brazilian states Rondônia and Piauí, and subsequently reared to adults. Larvae and pupae are illustrated and photomicrographed. Details on the rearing process and feeding behavior in laboratory, bionomics and notes on habitats are also provided.